(untitled) (Journal of Atomic and Molecular Sciences, 2010)
Lithium silicates, such as Li_2SiO_3 and Li_4SiO_4, are considered as favorable candidates for the tritium breeding materials of a nuclear fusion reactor. Their bulk electronic properties and mechanics are important for the tritium behavior and tritium breeding blanket designs. We have studied the structural and electronic properties of Li_2SiO_3 and Li_4SiO_4 bulks using density functional theory (DFT) within generalized gradient approximation (GGA). The calculated crystal parameters are well consistent with the experimental results. The electronic band energy calculations show that Li_2SiO_3 and Li_4SiO_4 are insulators with a band gap of about 5.36 and 5.53 eV, respectively. Their valence band properties are mainly determined by the oxygen 2p orbital electrons. The two types of oxygen atoms, nonbridging oxygen (NBO) atoms and bridging oxygen (BO) atoms, in Li_2SiO_3 reveal significantly different electron distribution of oxygen 2p orbital. The Si 3s and 3p hybridization is observed in Li_2SiO_3, but not in Li_4SiO_4. In both lithium silicates, the electronic density increases more steeply around Li and Si atom sites compared with that around O atoms. Additionally, the mechanical properties of both lithium silicates were calculated and discussed first time.